ANALISIS BEBAN KERJA DAN LINGKUNGAN TERHADAP KEPUASAN KERJA KARYAWAN MASA PANDEMI COVID-19 (Studi Kasus Pada UMKM Kuliner di Yogyakarta) - Agus Dwi Cahya; Rizka Dwi Astuti; Dewi Palupi (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Abstract The purpose of this study was to determine the effect of workload and work environment on employee job satisfaction during the Covid-19 Pandemic. This type of research is a descriptive study with a quantitative approach. The subjects of this study were employees of the Merapi Coffe, Galia Cofee and Nyegerin.id MSMEs in the Yogyakarta area. Primary data obtained from a questionnaire with 37 respondents with the Non Probability Sampling technique using saturated sampling. Then the data were analyzed using multiple linear regression analysis. The results of the research on the t test show that the workload variable (X1) has a negative and insignificant effect on the job satisfaction variable (Y) with a significance value of 0.333 and the work environment variable (X2) has a positive and significant effect on job satisfaction (Y) with a significance value of 0.003. The results of the study with the F test showed that the workload variable (X1) and the work environment (X2) had a simultaneous effect on job satisfaction with a significance value of 0.010. Keywords: Workload, WorkEnvironment, JobSatisfaction